2008
DOI: 10.1111/j.1471-6402.2007.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the Schedules of Racist and Sexist Events: Confirmatory Factor Analyses of African American Women's Responses

Abstract: Use of the Schedule of Racist Events (SRE; Landrine & Klonoff, 1996) and the Schedule of Sexist Events (SSE; Klonoff & Landrine, 1995) has advanced research on experiences of perceived racism and sexism. The present study responds to calls for further investigation of the structural properties of data from these instruments and is the first study to do so using (a) responses of African American/Black women (N= 246) and (b) confirmatory factor analysis. Regarding the SRE, results supported the unidimensional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 53 publications
(147 reference statements)
8
21
1
Order By: Relevance
“…In addition, the significant correlation between the attributions to race/ethnicity and gender should not be overlooked. Similar to other studies that have found a significant overlap in race/ethnicity‐ and gender‐related constructs (e.g., discrimination; DeBlaere & Moradi, ), this investigation seems to support the assertion that important aspects of identity are significantly related and may subsume one another. Intersectionality scholars are only beginning to clarify how to conceptualize the overlap in attributions among different identities (DeBlaere, Brewster, Sarkees, & Moradi, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, the significant correlation between the attributions to race/ethnicity and gender should not be overlooked. Similar to other studies that have found a significant overlap in race/ethnicity‐ and gender‐related constructs (e.g., discrimination; DeBlaere & Moradi, ), this investigation seems to support the assertion that important aspects of identity are significantly related and may subsume one another. Intersectionality scholars are only beginning to clarify how to conceptualize the overlap in attributions among different identities (DeBlaere, Brewster, Sarkees, & Moradi, ).…”
Section: Discussionsupporting
confidence: 89%
“…For example, in studies on gender and racial/ethnic discrimination, one identity often emerges as a unique predictor of psychological outcomes (e.g., DeBlaere et al, ). DeBlaere and Moradi () theorized that, for racial/ethnic minority women, gender discrimination may evoke unique reactions relative to racial discrimination. That is, one often encounters racial discrimination from out‐group members in general, whereas racial/ethnic minority women may experience gender discrimination both within and outside of their racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I. Jones, Cross, & DeFour, 2007;Kwate et al, 2003). The SRE's structure has been supported in two evaluation studies (DeBlaere & Moradi, 2008;. Adequate internal consistency for the three SRE sub scales has also been supported in other investigations (e.g., Landrine & Klonoff, 1996;H.…”
Section: The Schedule Of Racist Eventssupporting
confidence: 54%
“…In addition to conceptual problems, high intercorrelations between the Recent, Lifetime, and Appraised Stressfulness subscales have been reported in some investigations (e.g., DeBlaere & Moradi, 2008;Fischer & Shaw, 1999). Researchers who have used the SRE commonly make decisions regarding the use of scale scores to minimize problems with redundancy, such as using only one scale score or using scores for only two of the three subscales (e.g., Fischer & Shaw, 1999).…”
Section: The Schedule Of Racist Eventsmentioning
confidence: 99%